Eksperimentalni razvojni sistem za mobilno robotsko platformo - Čepon, Peter (Ventil (Ljubljana), 2007)
In this paper an experimental development system for mobile robotic platform is presented. The development system incorporates the main controller, the drive unit with drive and steering wheel, the drive controller and development environment. The software development and supervision of execution is performed on the host main computer. The target embedded controller running xPC Target real time operating system is used for execution of the developed program in real time on a target system. The target controller communicates with the drive units via CAN communication. The development system is based on Mathworks Matlab tools Simulink, Stateflow and xPC Target. This configuration allows the development of control algorithm in graphical mode by building and connecting functional blocks. In this way the development system is built providing user friendly graphical software development environment, optimal tuning of parameters, acquisition and logging of signals, and easy incorporation of new devices.
Keywords: mobilna robotska platforma; razvojni sistem; Simulink; Stateflow; vodilo CAN